Health, illness, and use of care the impact of social factors - Kronenfeld, Jennie J. (Research in the sociology of health care, 2000)
This text explores the impact of social factors on health, illness and the use of care. Contributors examine a number of social factors including sex, gender and socio-economic status on the healthcare experience and focus on both patients within the care process and the providers of care. It also presents papers employing a variety of methodological approaches. In the range of illnesses discussed, the social factors under consideration, and the variety of methodological approaches, this volume represents the diversity within the field of medical sociology.